Effect of gamma irradiation on the change of solubility and anti-inflammation activity of chrysin in macrophage cells and LPS-injected endotoxemic mice. (October 2016) - Byun, Eui-Baek; Jang, Beom-Su; Byun, Eui-Hong; Sung, Nak-Yun
Abstract: This study evaluated the changes of solubility and anti-inflammatory properties of structurally modified gamma-irradiated chrysin. Chrysin was irradiated at various doses for a physical analysis and determining any structural changes and solubility. As shown through the physical analysis, the main peak of the chrysin was decreased as the irradiation dose increased, and it was concomitant with the appearance of several new peaks, which were highly increased in 50 kGy gamma-irradiated chrysin. The solubility was markedly increased in the gamma-irradiated groups. As shown through a physiological analysis, both gamma-irradiated- (15–50 kGy) and intact-chrysin (0 kGy) did not exert cytotoxicity to bone-marrow derived macrophages. The treatment of LPS-stimulated macrophages with 50 kGy gamma-irradiated chrysin resulted in a dose-dependent decrease in pro-inflammatory mediators, such as iNOS-mediated NO, PGE2, COX-2, and cell surface marker (CD80 and CD86), as well as pro-inflammatory cytokines (TNF-α and IL-6), when compared to the intact-chrysin treated group. Mechanically, we found that the inhibition of these pro-inflammatory mediators induced by gamma-irradiated chrysin occurred through an inhibition of MAPKs (ERK1/2 and p38) and the NF-κB signaling pathways. Furthermore, the anti-inflammatory activity remained in the LPS-injected animal model. In this model, gamma-irradiated chrysin treatment highly increased the mouse survival, and significantly decreased the serum cytokine (TNF-α, IL-6 and IL-1β) levels. From these findings, the anti-inflammatory action by gamma-irradiated chrysin may be closely mediated with structural modification. It seems likely that gamma irradiation can be an effective tool for improvement of the physical and physiological properties of polyphenols. Highlights: Gamma irradiation leads to the structural modification of chrysin. Gamma irradiation improved the solubility of chrysin. Gamma-irradiated chrysin significantly inhibited the inflammation mediator. Anti-inflammation mechanism involved the modulation of MAPKs and NF-κB. Gamma-irradiated chrysin attenuated the endotoxin-induced lethality.